Compton mechanism of W and Z boson hadroproduction - Bondarenco, M.V. (Вопросы атомной науки и техники, 2012)
It is argued that W/Z boson production in ultra-relativistic pp collisions in the fragmentation region, subject to a kinematic cut on the boson transverse momentum Q┴ > Q┴min, with 1 GeV/c << Q┴min, << MW/Z, must be dominated by the Compton mechanism qg → q'W/Z. We propose applications for boson hadroproduction in this kinematics, formulate the factorization theorem, and analyze the QCD enhancements.